Note on Casuarina Equisetifolia Plantation in Karwar - Kaikini, D. S. (Indian Forester, 1937)
The casuarinas first Introduced in Karwar in 1868-69 on a small scale now cover 431 acres of narrow sand belt along the coast. The supply of fuel, protection from high winds and storms and aesthetics are among the objects for the plantations. Clear-felling by 15 years’ rotation and artificial planting are adopted with two thinnings in fifth and tenth years.